An International Survey on the pragmatic management of epistaxis - Passali, Desiderio; Damiani, Valerio; Passali, Francesco Maria; Tosca, Maria Angela; Motta, Gaetano; Ciprandi, Giorgio (Acta Biomedica Atenei Parmensis, 2020)
Epistaxis is one of the most common ear, nose and throat emergencies. The management of epistaxis has evolved significantly in recent years, including the use of nasal cautery and packs. However, a correct treatment requires the knowledge of nasal anatomy, potential risks, and complications of treatment. Epistaxis is often a simple and readily treatable condition, even though a significant bleed may have potentially severe consequences. At present, there are very few guidelines concerning this topic. The current Survey explored the pragmatic approach in managing epistaxis. A questionnaire, including 7 practical questions has been used. The current International Survey on epistaxis management reported a relevant prevalence (21.7%), mainly during childhood and senescence, an important hospitalization rate (11.8%), the common use of anterior packing and electrocoagulation, and the popular prescription of a vitamin supplement and intranasal creams.